2016
DOI: 10.1007/s00256-016-2414-7
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution CT of the sternoclavicular joint and first costochondral synchondrosis in asymptomatic individuals

Abstract: In asymptomatic patients, there is no significant asymmetry of the SCJ. The joint spaces did not significantly decrease with age, although such a trend could be observed. Pronounced joint space narrowing with large geodes and osteophytes was not seen. Clefts of the first costochondral junction are common and not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, the work done by De Maeseneer et al 11 revealed no significant difference between the joint distances of both SCJ. That study was performed retrospectively through carotid CT angiography images, where patients were kept in neutral position during image acquisition 11 . Additionally, that study reported that joint distance might show a slight decrease with aging, with degenerative signs showing an equal distribution on the sternal and clavicular surfaces.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…However, the work done by De Maeseneer et al 11 revealed no significant difference between the joint distances of both SCJ. That study was performed retrospectively through carotid CT angiography images, where patients were kept in neutral position during image acquisition 11 . Additionally, that study reported that joint distance might show a slight decrease with aging, with degenerative signs showing an equal distribution on the sternal and clavicular surfaces.…”
Section: Discussionmentioning
confidence: 81%
“…In a study where SCJ distances were examined with CT it was reported that there may be an asymmetry up to 5.7 mm between both joints 10 . However, the work done by De Maeseneer et al 11 revealed no significant difference between the joint distances of both SCJ. That study was performed retrospectively through carotid CT angiography images, where patients were kept in neutral position during image acquisition 11 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A CT morphological description of the SCJ width was previously performed in healthy patients [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%